Listening to Teachers: CEFR implementation in University Language Centres in Spain - Gloria Luque Agulló; María Belén Díez-Bedmar (Revista de Lingüística y Lenguas Aplicadas, 2025)
Despite the widespread reference to the Common European Framework of Reference for Languages (CEFR) and the Companion Volume (CV) in the language teaching curriculum in Spain, there is no information regarding teachers’ familiarity with the documents and their degree of implementation in University Language Centres, crucial for he  internationalization of universities. To bridge this gap in the literature, a questionnaire was designed, validated and administered to sixty-four teachers from 14 different Centres throughout Spain. Findings reveal gaps in the teachers’ knowledge regarding differences between the documents, specific issues related to the CV, and varying degrees of familiarity and use of competences and their descriptors. A further analysis of open questions also revealed those aspects which are missing in teacher training. The results obtained may be used to inform continuous teacher training to improve CEFR/CV implementation in University Language Centres in Spain, aligning their teaching practice to the documents.